Nutrients balances and milk fatty acid profile of mid lactation dairy cows supplemented with unsaturated fatty acid - Freitas Júnior, Jose Esler de; Rennó, Francisco Palma; Gandra, Jefferson Rodrigues; Rennó, Luciana Navajás; Rodrigues, Gustavo Henrique; Santos, Marcos Veiga dos; Oliveira, Mauro Dal Secco de [UNESP] (FapUNIFESP (SciELO), 2013)
The objective was to evaluate the effect of unsaturated fatty acid sources supplementation on nutrients balances and milk fatty acid profile of mid lactation dairy cows. Twelve Brazilian Holstein cows in the mid lactation (mean of 128 days) and (580 ± 20kg of weight; mean ± SD) with milk yield of 25kg/d were assigned randomly into three 4 × 4 Latin square, fed the following diets: control (C); refined soybean oil; (SO); whole soybean raw (WS) and; calcium salts of unsaturated fatty acids (CSFA). Milk yield was 26.6; 26.4; 24.1 and 25.7 to the diets CO, SO, WS and CSFA respectively. Cows fed the WS treatment produced less milk (1.95kg/d of milk), fat and lactose than did cows fed the SO and CSFA. Cows fed the CSFA treatment showed less blood, urine (g/d) concentrations of N more energetic efficiency and intake of energy than did cows fed the SO treatment. Cows fed the unsaturated fatty acids sources showed more C18:2 cis-9, trans-11 CLA and trans-C18:1 FA concentration in milk than did cows fed the CO treatment. Diets with whole soybeans and soybeans oil provide more efficient digestive processes, and increase milk composition of unsaturated fatty acids.
Keywords: Digestibility; Lipids; Performance; Whole raw soybeans